Application Manual of Geophysical Methods to Engineering and Environmental Problems - Aizawa T. Takao (Houten, EAGE, 2014)
This book is a comprehensive manual of shallow geophysical surveys for engineering and environmental applications. It describes details of applicability and limitation, field procedure, analysis and interpretation of geophysical methods in simple terms. Keep this manual on your desktop and refer to it from time to time to improve the quality of your work in construction engineering and environmental maintenance. This manual of geophysical surveys describes the standard procedure of practice rather than the basic theories of geophysical methods. Its intention is to share our experience with young geophysicists who collect and analyze geophysical data and clients who use results of geophysical surveys. It describes standard operational procedure of data acquisition and analysis in each method to reach a sound interpretation of the data. It also includes a due consideration on performance efficiency, quality control and reporting. Geophysicists may refer to this manual in all the stages of a survey: data acquisition, processing, analysis and interpretation. To the clients of the survey, this manual may be particularly useful in understanding the surveys from planning to assessing the outcome: how data are presented.